Diagnostic Dilemma in Allergy and Coronary Syndromes: Kounis Syndrome or Adrenaline Effect? - Ebru Atike Ongun; Nilgün Erkek; Fırat Kardelen; Ayşen Bingöl; Oğuz Dursun (Galenos Yayinevi, 2018)
Management of anaphylaxis includes adrenaline, a life-saving drug, however appropriate dosing and administration are of crucial importance due to serious side effects. We present a 15-year-old female with anaphylactic reaction manifesting as acute coronary syndrome and pulmonary edema following the administration of adrenaline as an intravenous bolus. Focusing on anaphylaxis, adrenaline and coronary symptoms, this report discussed the interactions between three intertwining entities: Kounis syndrome, Takotsubo cardiomyopathy, and adrenaline-induced coronary vasospasm, and challenges in differential diagnosis. Brugada syndrome (cardiac autonomic dysfunction) and clinical manifestation of the patient was also evaluated. Early consideration of adrenaline at the appropriate dose and administration route is essential in anaphylaxis management. Kounis syndrome should be considered in those presenting with allergy symptoms and chest pain and adrenaline should be used carefully due to possible risks of worsening coronary symptoms in patients with Kounis syndrome. This report also highlights a very rare side effect of adrenaline; the drug, which constitutes the cornerstone of anaphylaxis management, has a potential to trigger allergy itself due to metabisulfite-containing preservative.